Analisis Batubara Jenis Antrasit di PTBA Berdasarkan Kandungan Volatile Matter dan Kalori - Yohanes W.M Purba; Pulung Karo Karo; Ediman Ginting (Journal of Energy, Material, and Instrumentation Technology, 2020)
This research Coal is one of the sedimentary fossil fuels that can ignite, is formed from organic sediment, and the remains of plants are then formed through the process of coalification. The main element consists of carbon, hydrogen, and oxygen. The formation of coal has certain conditions and only occurs in certain eras throughout geological history. The carbon age was approximately 340 million years ago. In the Permian Age or the Paleozoic era, 270 million also formed the most productive coal which is almost the entire coal deposit (black coal) in other parts of the earth. In this study we conducted at the Laboratory of PT. Bukit Asam tbk. Observation Results in the Study of Average Volatile Matter 19.11, Max Volatile Matter value 38.34, Min Vollatie Matter value 11.34. And the Average Calorie Result of 7578.5 Kacl / Kg, Max Calorie Value of 8046 Kcal / Kg. In this study, it was proved that coal samples were Anthracite types.